An Analysis of Connotative Meaning on Justin Bieber’s Song Lyrics - Ita Purnamasari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
Semantics is the study of the meaning of words, phrases and sentences. Connotative meaning can be found in literary work including song lyrics. A song can also become a media to introduce social values. In this study, the researcher focus on connotative meaning using Chaer’s (2013) theory and sense a values of American people using theory by Khols (1984). The data source in this study are Justin Bieber’s song lyrics. This research was done by analyzing the data qualitatively. Techniques of data collection are done by downloading the song and the lyrics, listening the song, reading the lyrics and watching the videos. Data analysis was done by adapting Miles and Huberman’s theory (1984). The step of data analysis are: reduction of data, display of data, verification of data and conclusion. The result of the research describe words contain connotative meaning and values of American people. The total of data contain connotative meaning are sixteen, six words include in equality/egalitarianism Americans values, four words include in material/acquisitiveness American values, one word include in time and its control American values, three words include in change American values and one word include in self-help concept American values.